(untitled) (The Agriculturists, 2016)
A study was conducted in the laboratory of the Department of Seed Pathology, Sher-e-Bangla Agricultural University, Bangladesh during July 2013 to June 2014 to determine the effects of different storage containers and durations of storage on the quality of okra (Abelmoschus esculentus) seeds and seedling growth. After harvest, seeds were stored in earthen pots, plastic pots, plastic bags, gunny bags with and without polyethylene lining for the periods of 4, 8, and 12 months. The seeds stored in plastic container showed the lowest moisture content (8.03%) at 4 months of storage and those stored in gunny bag showed the maximum moisture content (17.63%) at 12 months of storage. Percentage of seeds infested with fungi was minimum in plastic container, where the prevalence of Fusarium spp., Chaetomium globosum, Aspergillus flavus, Aspergillus niger, Rhizopus stolonifer and Curvularia spp. were 1.47, 8.03, 3.31, 3.31, 2.57 and 3.53%, respectively at 4 months of storage. Prevalence of fungi was maximum in seeds stored in gunny bag where the prevalence of Fusarium spp., Chaetomium globosum, Aspergillus flavus, Aspergillus niger, Rhizopus stolonifer and Curvularia spp. were 4.87, 17.63, 4.41, 5.97, 84.86 and 5.19%, respectively at 12 months of storage. In contrast, treated seeds stored in plastic container showed the maximum germination (94.74%), longest shoot (20.76 cm) and root (11.52 cm), highest seed vigor index (3087.00), highest weight of dry seedlings (55.60 g) at 4 months of storage. However, seeds stored in gunny bag showed the lowest seed germination (45.08%), shoot length (11.49 cm), root length (6.34 cm), seedling vigor index (838.10), dry weight of seedlings (33.40 g) and field emergence (37.36%) at 12 months of storage. Plastic containers appeared to be the best for storage of okra seeds. The Agriculturists 2016; 14(1) 63-72